Validation of NCM460 cell model as control in antitumor strategies targeting colon adenocarcinoma metabolic reprogramming: Trichostatin A as a case study - Alcarraz-Vizán, Gema; Sánchez-Tena, Susana; Moyer, Mary Pat; Cascante, Marta (Biochimica et biophysica acta, 2014)
Cancer cells have extremely active metabolism, which supports high proliferation rates. Metabolic profiles of human colon cancer cells have been extensively studied, but comparison with non-tumour counterparts has been neglected. Here we compared the metabolic flux redistribution in human colon adenocarcinoma cells (HT29) and the human colon healthy cell line NCM460 in order to identify the main pathways involved in metabolic reprogramming. Moreover, we explore if induction of differentiation in HT29 by trichostatin A (TSA) reverts the metabolic reprogramming to that of NCM460. Cells were incubated with [1,2-(13)C2]-d-glucose as a tracer, and Mass Isotopomer Distribution Analysis was applied to characterize the changes in the metabolic flux distribution profile of the central carbon metabolism. We demonstrate that glycolytic rate and pentose phosphate synthesis are 25% lower in NCM460 with respect to HT29 cells. In contrast, Krebs cycle activity in the former was twice that recorded in the latter. Moreover, we show that TSA-induced HT29 cell differentiation reverts the metabolic phenotype to that of healthy NCM460 cells whereas TSA does not affect the metabolism of NCM460 cells. We conclude that pentose phosphate pathway, glycolysis, and Krebs cycle are key players of colon adenocarcinoma cellular metabolic remodeling and that NCM460 is an appropriate model to evaluate the results of new therapeutic strategies aiming to selectively target metabolic reprogramming. Our findings suggest that strategies to counteract robust metabolic adaptation in cancer cells might open up new avenues to design multiple hit and targeted therapies.